The relationship between psychosocial work conditions and employee health in Cyberview Sdn Bhd and the subsidiaries - Raspan, Ainil Hawa (2018)
The purpose of this study is to examine and gain a better understanding of employees health in relation to psychosocial work conditions at Cyberview Sdn Berhad and the subsidiaries. Psychosocial is one of the health aspects that can contribute to the overall health of the individual. This health is closely related to mental health and social function. Conditions such as emotional and stress problems contribute significantly to mental health and social functions. To produce good jolJ performance, organisation needs to create a psychosocial environment that can make individuals feel comfortable to be in groups and organisations, showing high participation, high productivity and quality improvement work. In order to understand the real situation due to the trend in increasing numbers of leave absence taken by employees due to health problems occurred in the organisation, this study were expected to assist management of an organisation to understand the status and health problems and are award of their relevance to productivity and try to address the problem through related programs. Data were collected from the organisations comprises with 92 respondents. Questionnaires were used and analysed using Statistical Package for Social Science (SPSS) version 21. Using correlation analysis, it was found that there is a significant relationship between the independent variable, psychosocial work conditions with the dependent variable, employees' health in Cyberview Sdn Bhd and its subsidiaries.